Do ageist attitudes affect home care workers' job satisfaction and retention?. Issue 8 (3rd August 2022) - Liu, Chien-Chih; Liu, Li-Fan
ABSTRACT: With the rapid increase of older adults, attracting and retaining home care workers in the long-term care system will be critical to meet demands. This study examined how intrinsic and extrinsic factors of job satisfaction affect home care workers' intention to stay and determined whether ageist attitudes had a mediating effect on the relationship between job satisfaction and intention to stay. The stratified random cluster sampling method was applied in this study and self-administered questionnaires were distributed to 400 home care workers from home service units in one city in southern Taiwan. Overall, 380 participants completed the measures of job satisfaction, ageist attitudes, and intention to stay in their current job. The monthly wages of NT$30, 000 to NT$39, 999 were significantly related to home care workers' intentions to stay. Both intrinsic and extrinsic factors of job satisfaction were significantly associated with the retention of home care workers. However, the ageist attitudes' separation and affective attitude factors were mainly related to their intention to stay. Ageist attitudes have a significant mediating effect between the intrinsic factors of job satisfaction and intention to stay but have no significance for extrinsic factors. Therefore, we suggested that improving the extrinsic and intrinsic factors of job satisfaction could increase the retention of home care workers. Additionally, providing accurate aging-related knowledge to raise awareness of ageist attitudes may enhance the relationship between the intrinsic factors of job satisfaction and retention. These findings could be valuable for improving the retention of the workforce in long-term care.